Enter the body : women and representation on Shakespeare's stage - Rutter, Carol Chillington (Routledge, 2001)
'Enter the Body' offers a series of provocative case studies of the work women's bodies do on Shakespeare's intensely body-conscious stage. Rutter's topics are sex, death, race, gender, culture, politics, and the excessive performative body that exceeds the playtext it inhabits. As well as drawing upon vital primary documents from Shakespeare's day, Rutter offers close readings of women's performance's on stage and film in Britain today, from Peggy Ashcroft's (white) Cleopatra and Whoopi Goldberg's (whiteface) African Queen to Sally Dexter's languorous Helen and Alan Howard's raver 'Queen' of Troy.